The Reception of Plato’s Phaedo in Philo of Alexandria (Circe de clásicos y modernos, 2018)
The knowledge and use of the Phaedo by Philo is an important source of information about its interpretation at that time. We must take into account that Philo never makes any direct references to the Phaedo but does quote a few snippets. However, Plato’s use of language has influenced Philo, particularly in the rich use of compound adjectives. Philo draws a copi-ous harvest of images from the dialogue: a) the image of the body as a prison; b) the image of the body as a garment for the soul; c) the bondage that the soul must endure through its association with the body; and d) the journey abroad (ἀποδημία) to another place (Phaedo67c), which is linked to the biblical theme of migration. Other general themes in the dialogue are also explored, such as the descent of the soul into the body in terms of metempsychosis or reincarnation. Finally, four passages are discussed: Leg. 1. 105-108, Gig. 13-15, Somn. 1. 138-139 and Her. 267-276.
Keywords: Plato; Phaedo; Philo; soul; body